치과위생사의 건강관리 및 의료 이용 행태에 관한 조사 연구 - 윤미숙; Mi Sook Yoon; 이경희; Kyung Hee Lee (Chiwisaeng gwahakoeji, 2004)
The purpose of this study was to examine how dental hygienists health management and to what extent they used medical care services due to occupational diseases. It's ultimately attempted to improve the health care of dental hygienists and promote their health. After relevant literature and data were reviewed, a survey was conducted for five months from June through October, 2003. The subjects in this study were 160 dental hygienists who worked at dental hospital and clinics across the nation. And the collected data were analyzed. The findings of this study were as follows: (1) Concerning job-related health education experience, 83.1 percent, the greatest rate, had no experience to receive education, and the type of service made a significance difference to that(p<0.05). (2) As to in-house medical examination, 98.6 percent felt the need for medical examination, and 56.3 percent had ever their bodies examined. Their health examination experience was significantly different according to age(p<0.01), marital status(p<0.01), type of service(p<0.01), career(p<0.01) and yearly income(p<0.01). (3) Concerning how much they used hospitals after working as dental hygienists, 85.6 percent, the biggest group, had no experience to be hospitalized, and that was significantly different according to age(p<0.05), type of service(p<0.05), career(p<0.01) and yearly income(p<0.05). 51.9 percent had no experience to receive treatment as outpatients, and their career(p<0.01) made a significant difference to that. (4) As for how to cope with casual diseases, 34.4 percent, the largest group, visited pharmacies, and 32.5 percent, the next largest group, saw the doctors. In regard to herb restorative, 68.1 percent had no experience to take herb restorative, and that experience varied significantly with age(p<0.01), career(p<0.05) and annual income(p<0.01). 치과위생사의 효율적인 건강관리와 건강증진을 위한 기초 자료로서 활용하고자 문헌과 자료를 조사하고 전국 치과 병, 의원에 종사하는 치과위생사 160명을 대상으로 2003년 6월부터 10월까지 약 5개월 동안 의료 이용 행태에 관한 설문조사를 실시하여 분석한 결과 다음과 같은 결론을 얻었다. 1. 직업과 관련된 건강 교육 경험 여부를 살펴본 결과, 교육의 경험이 없는 치과위생사가 83.1%로 가장 많았고, 근무 형태에 따라(p<0.05) 통계적으로 유의미한 차이를 보였다. 2. 직장 내 건강 검진 실태를 살펴본 결과, 건강 검진의 필요성에 대해서는 98.6%가 필요하다고 인식하였고, 건강 검진 실시 여부에 대해서는 56.3%가 건강검진의 경험이 있는 것으로 조사되었으며, 연령에 따라(p<0.01), 결혼상태에 따라(p<0.01), 근무형태에 따라(p<0.01), 근무경력에 따라(p<0.01), 연간수입에 따라(p<0.01) 통계적으로 유의미한 차이를 보였다. 3. 치과위생사로의 재직 후 병원 이용실태를 살펴본 결과, 병원 입원 경험이 없다고 응답한 치과위생사가 85.6%로 가장 많았고, 연령에 따라(p<0.05), 근무형태에 따라(p<0.05), 근무경력에 따라(p<0.01), 연간수입에 따라(p<0.05) 통계적으로 유의미한 차이를 보였으며, 외래 진단 경험은 없다고 응답한 치과위생사가 51.9%로 나타났고, 근무경력에 따라(p<0.01) 통계적으로 유의미한 차이를 보였다. 4. 가벼운 질병에 대한 대처 방법으로 약국을 찾는 경우가 34.4%로 가장 많았고, 다음으로 의원 및 병원 방문이 32.5%로 나타났으며, 보약 복용 경험에 대해서는 복용 경험이 없다고 응답한 경우가 68.1%로 나타났고, 연령에 따라(p<0.01), 근무경력에 따라(p<0.05), 연간수입에 따라(p<0.01) 통계적으로 유의미한 차이를 보였다.